Adolescência, ato infracional e transgeneridade: um estudo de caso - Barbosa, Anna Líria Sansaloni (Universidade Federal de São Carlos, 2023)
Adolescence is often a neglected stage of human development. The opinions and perspectives of adolescents are more frequently than not left aside or evaluated from the perspective of the surrounding adults. This neglect is intensified with other characteristics the population may have that qualify them as a minority, such as being trans and facing several other stigmas. In the present research, this life stage and gender are perceived as social constructs built upon the development of peer interactions. Furthermore, it’s considered that the involvement in offending behavior is means to empower and create resilience to build identity. The general purpose of this research is to analyze the life context of a trans adolescent answering for offending behavior, for that matter, the researcher conducted a single case study through and ecological insertion and an interview that discussed themes such as identity, peer relationships, offending behavior and ways to manage power discrepancies. Through a thematic analysis of the data, results revealed a general profile of the adolescent and the context of his insertion in drug trafficking. It was identified that he nurtures a positive view of himself, despite requiring reaffirmation from peers and authority figures. Furthermore, some of the peers explored in the interview have major significance in the subject’s development and may be seen as resilience tutors, offering social support and encouragement. Despite the empowering role of the offending behavior, the research showed that the adolescent suffered through prejudice and discrimination for being trans in the trafficking environment. Through these results, it is possible to investigate new questions that arise and further understand the context of trans adolescents answering for offending behavior.
Adolescence, offensive conduct and transgender people: a case study
Keywords: Adolescência; Identidade; Transgeneridade; Ato infracional; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO DESENVOLVIMENTO HUMANO::DESENVOLVIMENTO SOCIAL E DA PERSONALIDADE